Effect of Ground Granulated Blast Slag and Temperature Curing on the Strength of Fly Ash-based Geopolymer Concrete - Kumar, Anil; Rajkishor, .; Kumar, Niraj; Chhotu, Anil Kumar; Kumar, Bhushan (Engineering, Technology & Applied Science Research, 2024)
Concrete is used most extensively after water to meet construction requirements. Since the population is increasing day by day, the demand for concrete will always increase, hence, the demand for cement will also increase. The production of cement requires a lot of energy and emits greenhouse gases into the environment. Therefore, an alternative material for cement concrete is required. Geopolymer concrete (GPC) is an alternative to cement made of aluminosilicate materials such as fly ash, Ground Granulated Blast Slag (GGBS), silica fume, metakaolin, etc. If these materials are activated with an alkaline activator, then a bond that is responsible for the strength develops. GPC made with fly ash needs temperature curing to develop its strength, which limits its use on a large scale. In this study, a mix ratio of GPC equivalent to conventional M20 concrete was obtained at ambient curing conditions. The effect of temperature curing was also studied. GPC was prepared in three different mixes. In each mix, the binder content was changed by varying the fly ash and GGBS content. Two sets of cube, beam, and cylindrical samples were prepared from each mixture. One set was cured at ambient temperatures and the other at increased temperatures. The temperature-cured specimens provided higher strength than the ambient-cured. If a strength equivalent to conventional M20 concrete is required for ambient curing, then the mix should be 70% fly ash and 30% GGBS, and the ratio of binder, fine aggregate, and coarse aggregate should be 1:1.5:3.